Religious Moderation Values in Islamic Religious Education Textbooks for Public Elementary Schools - Kensiwi, Noni; Subekti, Fiqi Restu; Wahid, Umar; Wibowo, Taufik Awan (South Sulawesi Education Development, 2026)
This study examines the presence of religious moderation values in Islamic Religious Education (PAI) textbooks for elementary students in Grades 1-6 and proposes strategies to strengthen the internalization of these values in classroom practice. The research adopts a qualitative approach through a literature-based study, analyzing PAI textbooks as primary sources and relevant scholarly works as supporting references. The primary data consist of PAI textbooks for Grades 1-6, which were examined in depth. The findings show that the presentation of religious-moderation values in the textbooks remains varied. Several materials include moderation values only implicitly, such as encouragement to act kindly or to care for others. Other sections present moderation values more explicitly, including respect for diverse backgrounds, tolerance toward Indonesia’s religious plurality, and appreciation of cultural, ethnic, and opinion-based differences. The study also identifies inconsistencies across grade levels, with some materials showing no indication of moderation values at all. Based on these findings, the study recommends strengthening moderation values through clearer learning outcomes, the use of supportive instructional activities (such as daily stories, emotion cards, or a friendly corner), and improved collaboration between teachers and parents to ensure consistent formation of moderation values.